Chemical Substances and in-Vivo Antiplasmodial Activity of Ageratum Conyzoides in Plasmodium Berghei Infected Mice - I.H. Ifijen; M. Maliki; O.K. Ogbeide; R.O. Okonkwo; S.O. Omorogbe; E.U. Ikhuoria (Journal of Applied Sciences and Environmental Management, 2019)
Malaria afflicts millions of people globally, particularly in tropical Africa; it is transmitted to humans through a bite of an Anopheles mosquito. Phytochemical, acute toxicity and in-vivo antiplasmodial activity of the leaves of Ageratum conyzoides were examined to study its effects on Mice that have been infected with the malaria parasite. Phytochemical screening of the methanol extract revealed the presence of secondary metabolites such as terpenoids, flavonoids, alkaloids, steroids and chromene. The LD50 was established at ˃ 1000 mg/kg body weight of mice. The methanol extract of A. conyzoides displayed intrinsic prophylactic and curative anti-malaria activity. At 200 mg/kg and 100 mg/kg body weight of mice, the extract revealed the highest percentage inhibition (83 and 61) for the prophylactic and curative study respectively. The acute toxicity study showed that A. conyzoides extract is relatively safe within the study administered doses. The methanol extract of the prophylactic study against Plasmodium berghei revealed an increase in the level of significance at administered portions of 100, 200 and 400 mg/kg in comparison with 0.2 ml distilled water and 10 mg/kg chloroquine. The methanol extract of the therapeutic study against Plasmodium berghei revealed a slight increase in the level of significance at administered doses of 100 and 200 mg/kg, however, no significant effect was observed for 400 mg/kg compared to the negative control and reference drug. The outcome implies that methanol leave extract of A. conyzoides possesses meaningful antiplasmodial activities and could be a promising source of novel antimalarial.